A study of the decay of acid cationic ion exchange resin - Nesbitt, Allan Bernard (Department of Chemical Engineering, 2017)
A study was undertaken on the decay of acid ion exchange resin from both a qualitative and quantitative perspective. The qualitative study concentrated on observing the impact on resin strength of varying electrolyte concentrations and varying di-vinyl benzene contents, during the loading phase. The phenomenon of osmotic shock in addition to resin cracking and swelling is clearly observed. A further qualitative study bore out the change in resin rigidity as the resin is artificially degraded through repeated loadings and regenerations performed by using a specially constructed device that cyclically loads and regenerates resin up to 1000 times in a three week period. Loss of resin rigidity was observed under these circumstances and was measured by means of observing changes in degree of swelling/contraction and changes in translucence. Quantitative study of the resin was limited to its characterisation through measurement of the equilibrium through the Mass-Action Law, capacity and resin kinetics. A study, of existing kinetic rigorous modelling methods and in particular the extensively published challenge of the multiple mechanism adsorption process, was undertaken. A rigorous model, that divorces the external and internal mass-transport parameters from the traditionally utilised lumped parameter, is proposed. All kinetic measurements were performed in a 1 litre closed circuit (finite system) consisting of a variable-pump, a five mL zero length column (ZLC) and a reservoir, allowing for the insertion of probes and sample extraction. An original method of model simulation for the purposes of fitting to kinetic data was developed and consists of determining the resin surface concentration from flux data assuming the applicability of Newton's Law of Cooling to the ionic flux through the external laminar layer. Simulation of flux inside the resin was achieved by assuming an internal homogeneous environment and the applicability of the Nernst-Plank equation that combines transport effects of both Fick's Law of Diffusion and inter-ion electrical forces to the flux of both the adsorbing and desorbing ions simultaneously, during the transient adsorption process.